Permasalahan dan Potensi dalam Diseminasi Official Statistics pada Badan Pusat Statistik - Sabriella Hafifah; Waris Marsisno (Politeknik Statistika STIS, 2022)
Badan Pusat Statistik is a Non-Ministerial State Institution appointed as the Advisor for Statistics in Indonesia. In this case, BPS has an important role in producing quality statistical data (official statistics) according to existing standards. Statistical results or products from BPS certainly need to be disseminated to data users or data consumers. Dissemination of statistical results is called dissemination. The official statistics data dissemination process at BPS has been going well, but based on the BPS Data Needs Survey (SKD) in 2021, data consumer satisfaction has reached a satisfied number but there are still some aspects or service attributes that are not satisfied. Therefore, it is necessary to examine what problems arise and cause the percentage of data user satisfaction with BPS data and services. Then look at and identify the potential that exists to continue to develop the data dissemination process at BPS. It was found that the problems that arise in the dissemination process are the lack of data dissemination channels and also the lack of utilization of information and communication technology in the dissemination of official statistics data. The potential that needs to be strengthened is the addition of a marketing strategy or promotion of official statistics data in accordance with the targets and needs of BPS data users.